Increasing coverage of vaccination by pharmacists in Nigeria; an urgent need - Yusuf Hassan Wada; Muhammad Kabir Musa; Aniekan Ekpenyong; Yusuff Adebayo Adebisi; Mohamed Babiker Musa; Garba Mohammed Khalid (Elsevier, 2021)
Pharmacists have a key role to play to advance public health through immunization. Pharmacists are well trained and play a huge role in vaccine production, research and development, safety, pharmacovigilance, storage, logistics and distribution. There is a need for a revised national policy and strategy in Nigeria on vaccination and immunization programs with the involvement of community pharmacies and/or pharmacists. This will help accelerate getting a wider vaccination access coverage, establishing a greater healthcare delivery workforce for societal benefits and demonstrate the full potential of the community pharmacies and the pharmacists' role in immunization programs.